Pendidikan Nilai Dalam Al-Quran - Adie Nugroho (Al-Riwayah : Jurnal Kependidikan, 2016)
This article studies about education of values according to the Holy Quran. The analytical tends to move from the Quranic verses by using the Quranic exegesis science approach. Instruments of analysis use multiple approaches, including semantic, particular external aspects, socio-historical approach, internal relationship, and so on. The Holy Quran pays a good attention to the education, particularly caracter building and internalization of core values. A caracter building, according to The Holy Quran, is built from inner awarness of the humen (anfus). The core values are internalyzed and actualyzed to build a good caracter. In this case, the Holy Quran shows alot of examples about historical facts in order that the human kinds find good morals which bring about core values or inner values. Hopely, those core values build a good attitude, a good caracter, intelect, and faithfull